Characterisation of a stereotypical cellular and extracellular adult liver progenitor cell niche in rodents and diseased human liver. Issue 5 (28th April 2010) - Lorenzini, Stefania; Bird, Thomas G; Boulter, Luke; Bellamy, Christopher; Samuel, Kay; Aucott, Rebecca; Clayton, Elizabeth; Andreone, Pietro; Bernardi, Mauro; Golding, Mathew; Alison, Malcolm R; Iredale, John P; et al.
Abstract : Background: Stem/progenitor cell niches in tissues regulate stem/progenitor cell differentiation and proliferation through local signalling. Objective: To examine the composition and formation of stem progenitor cell niches. Methods: The composition of the hepatic progenitor cell niche in independent models of liver injury and hepatic progenitor cell activation in rodents and humans was studied. To identify the origin of the progenitor and niche cells, sex-mismatched bone marrow transplants in mice, who had received the choline–ethionine-deficient-diet to induce liver injury and progenitor cell activation, were used. The matrix surrounding the progenitor cells was described by immunohistochemical staining and its functional role controlling progenitor cell behaviour was studied in cell culture experiments using different matrix layers. Results: The progenitor cell response in liver injury is intimately surrounded by myofibroblasts and macrophages, and to a lesser extent by endothelial cells. Hepatic progenitor cells are not of bone marrow origin; however, bone marrow-derived cells associate intimately with these cells and are macrophages. Laminin always surrounds the progenitor cells. In vitro studies showed that laminin aids maintenance of progenitor and biliary cell phenotype and promotes their gene expression (Dlk1, Aquaporin 1, γGT) while inhibiting hepatocyte differentiation and gene expression (CEPB/α). Conclusions: During liver damage in rodents and humans a stereotypical cellular and laminin niche forms around hepatic progenitor cells. Laminin helps maintenance of undifferentiated progenitor cells. The niche links the intrahepatic progenitor cells with bone marrow-derived cells and links tissue damage with progenitor cell-mediated tissue repair.